Effect of low-level ultrasound treatment on the production of L-leucine by Corynebacterium glutamicum in fed-batch culture. Issue 1 (1st January 2021) - Zhang, Yufu; Chen, Zhichao; Sun, Pengjie; Xu, Qingyang; Chen, Ning
ABSTRACT: Various process intensification methods were proposed to improve the yield, quality, and safety of fermented products. Here, we report the enhancement of L-leucine production by Corynebacterium glutamicum CP using ultrasound-assisted fed-batch fermentation. Response surface methodology was employed to optimize the sonication conditions. At an ultrasonic power density of 94 W/L, frequency of 25 kHz, interval of 31 min, and duration of 37 s, C. glutamicum CP produced 52.89 g/L of L-leucine in 44 h, representing a 21.6% increase compared with the control. The production performance of L-leucine was also improved under ultrasonic treatment. Moreover, the effects of ultrasound treatment on the fermentation performance of L-leucine were studied in terms of cell morphology, cell membrane permeability, and enzyme activity. The results indicate that ultrasonication is an efficient method for the intensification of L-leucine production by C. glutamicum CP. Graphical abstract: uf0001